CORRELATION INDICATORS OF CENTRAL HEMODYNAMIC WITH ANTHROPOMETRIC AND SOMATOTYPOLOGICAL PARAMETERS IN YOUNG VOLLEYBALL PLAYERS - Сарафинюк, Л.А.; Якушева, Ю.І. (World of Medicine and Biology, 2015)
Correlations between indicators of central hemodynamics, which were obtained by tetra polar reocardiography and anthropometric dimensions, components of somatotype and body weight in youth volleyball high level of sportsmanship, were established in the article. It was found that indicators of central hemodynamics have no reliable numerical relationships with constitutional characteristics, reliable correlation weak and medium strength are dominated.